1995
DOI: 10.1016/0926-6690(95)00027-a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of kenaf (Hibiscus cannabinus L.) seed oil

Abstract: Seeds from nine kenaf genotypes (Cubano, Everglades 41, Everglades 71, GR2563, Guatemala 48, Indian, 178-18RS-10, Tainung #l, and Tainting #2) were evaluated for oil, fatty acid, phospholipid, and sterol content. Oil content ranged from 21.4 to 26.4% with a mean of 23.7%. Total phospholipids ranged from 3.9 to 10.3% of the oil, with a mean of 6.0%. Mean sterol percent was 0.9 and ranged from 0.6% of the total oil for 178-18RS-10 accession to 1.2% for Everglades 71. Palmitic (20.1% of the total fatty acids), ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 15 publications
3
65
1
2
Order By: Relevance
“…Hydrocarbon compounds have been shown to exhibit antimicrobial activity (Kobaisy et al 2001;Ebije et al 2014). Kenaf seeds oil is used for margarine, and it is thus safe for human and animals (Mohamed et al 1995;Ghafar et al 2012;Alexopoulou et al 2013;Ghafar et al 2013;Ryu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrocarbon compounds have been shown to exhibit antimicrobial activity (Kobaisy et al 2001;Ebije et al 2014). Kenaf seeds oil is used for margarine, and it is thus safe for human and animals (Mohamed et al 1995;Ghafar et al 2012;Alexopoulou et al 2013;Ghafar et al 2013;Ryu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The seeds are also consumed to weight increase and bruises (Kubmarawa et al 2009;Alexopoulou et al 2013). The kenaf leaf and seed contains a variety of different compounds, including phenolic compounds, flavonoids, essential oils, and fatty acids (Mohamed et al 1995;Jin et al 2013;Ryu et al 2013;Nandagopalan et al 2015;Obouayeba et al 2015). Kenaf has been reported to exhibit properties associated with anodynes, aperitifs, aphrodisiacs, anti-inflammatory medications, and antioxidants for leaf and seed.…”
Section: Introductionmentioning
confidence: 99%
“…Linoleic acid was the most fatty acid components that can be found in kenaf seed oil, followed by oleic acid and palmitic acid. Similarly, Mohamed et al [4] also reported that kenaf seed oil consist of the highest percentage of linoleic acid, followed by oleic acid and palmitic acid, which were 45.9%, 29.2% and 20.1%, respectively.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…The high percentage of oleic acid in oil makes it desirable in terms of nutrition and high stability as cooking and frying oil. Furthermore, many studies had shown that kenaf seed oil has high potential as edible oil, due to its relatively high oil content and the unique fatty acid composition which is similar to cottonseed oil [4]. Besides, tocopherols were reported to be found in kenaf seed oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation